PENGARUH KONFLIK KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MUJUR TIMBER SIBOLGA - Giot Marito Simatupang; Mansur Tanjung; Nurainun Hasibuan (CV. ALIM'SPUBLISHING, 2023)
Writing this thesis aims to determine the effect of work conflict and workload on employee performance at PT. Lucky Timber Sibolga. The problem encountered in this study is the lack of a sense of mutual support in doing work as a team. The formulation of the problem in this study is whether there is an influence of work conflict and workload on employee performance at PT. Lucky Timber Sibolga? While the purpose of this study was to find out whether there is an influence of work conflict and workload on employee performance at PT. Lucky Timber Sibolga? The hypothesis put forward is that there is an influence of work conflict and workload on employee performance at PT. Lucky Timber Sibolga. The population in this study amounted to 525 people consisting of employees and contract employees, the sample in this study were 84 people. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is quantitative analysis. The results of the study found that work conflict and workload can affect employee performance at PT. It is known that Timber Sibolga has a coefficient of determination (R Square) of 0.605. Work conflict and workload together or simultaneously have a positive and significant effect on employee performance at PT. Lucky Timber Sibolga. Where is the Fcount > Ftable value (61.931> 3.11). Partially, work conflict has a positive and significant effect on employee performance at PT. Lucky Timber Sibolga. Where the value of tcount = (5.461) is greater than the value of ttable (1.989), Partially the most dominant workload affects performance, meaning that the workload variable is more decisive in improving employee performance compared to work conflict. Where the value of tcount = (8.886) > ttable value (1.989 ). Multiple linear regression equation Y = 11.315 + 0.315X1 + 0.511X2 employee performance shows a positive direction. It is recommended for companies to always try to control conflicts that occur in employees, namely by providing solutions to every problem that occurs in employees.